Oral manifestations of delusional infestation: a case series - Zahra Alsafwani; Morooj Aljishi; Caroline Shiboski; Richard Jordan; Alessandro Villa (BMC, 2022)
Abstract Background Delusional infestation (DI) is a rare psychotic disorder characterized by a patient's false belief that the body is infested with living or non-living organisms in the absence of clinical evidence of disease. Based on the underlying etiology, DI can be classified into primary and secondary forms based on the presence or absence of an underlying condition or previously diagnosed psychiatric disorder. This paper discusses a condition that is not commonly reported in the literature. Case presentation Here, we describe four patients diagnosed with DI of the oral cavity. In each case, the patients' intraoral examinations revealed either traumatic lesions or no signs of mucosal disease. Management involved symptom management, medical therapy, and/or a referral to the primary care provider. Conclusion Because oral health care providers may encounter patients with DI, they should familiarize themselves with this unusual condition in order to recognize the condition and initiate prompt referral to a psychiatrist.